Efectos del diferimiento del crédito tras la perturbación del covid-19 en la liquidez: estudio en la Cooperativa de Ahorro y Crédito “Fortuna” años 2019 y 2020. - Ordoñez Granda, María Fernanda (2022)
Credit deferral is a process of credit-obligations refinancing in which lending activities are restructured and renewed and people are given facilities to fulfill their future payments opportunely, without having to pay a delinquency charge, pay fines or change their default risk ratio. In this context, this research aims to analyze the effects of credit deferral after COVID19 affected liquidity in the “Fortuna” Credit Union from 2019 to 2020. The research was descriptive, quantitative, and non-experimental since credit deferral was analyzed, a correlational analysis between delinquency and liquidity was carried out, and a proposal for improvement was made. Hence, scientific, deductive, inductive, analytical, and synthetic methods were applied to support de analysis and proposal. The data collection instruments were observation and literature review. Then, the data were analyzed by using spreadsheets and PSPP software. The main findings showed that the credit deferral allowed the “Fortuna” credit union to have good liquidity and maintain a delinquency rate of approximately 3%. On the other hand, when the Pearson correlation coefficient was applied, a correlation coefficient of 1.7% was determined between delinquency and liquidity. Although, there was no statistical evidence to explain this relationship with the 5% level of significance. Finally, a proposal for improvement based on the financial analysis and internal and external factors was made to help improve the profitability of this credit union.